Levinas faces Kant, Hegel and Heidegger: Debates of contemporary philosophy on ontology - Xiushan, YE (Frontiers of philosophy in China, 2008)
Levinas subverts the traditional “ontology-epistemology,” and creates a “realm of difference,” the realm of “value,” “ethic,” and “religion,” maintaining that ethics is real metaphysics. According to him, it is not that “being” contains the “other” but the other way round. In this way, the issues of ethics are promoted greatly in the realm of philosophy. Nonetheless, he does not intend to deny “ontology” completely, but reversed the relationship between “ontology (theory of truth)” and “ethics (axiology),” placing the former under the “constraint” of the latter. Different from general empirical science, philosophy focuses more on issues irrelevant to ordinary empirical objects; it does have “objects,” though. More often than not, the issues of philosophy cannot be conceptualized into “propositions”; nevertheless, it absolutely has its “theme.” As a discipline, philosophy continuously takes “being” as its “theme” and “object” of thinking. The point is that this “being” should not be understood as an “object” completely. Rather, it is still a “theme-subject.” In addition to an “object,” “being” also manifests itself in an “attribute” and a kind of “meaning” as well. In a word, it is the temporal, historical, and free “being” rather than “various beings” that is the “theme-subject” of philosophy.